Expanded Reality: Just a Trend of our Time or do We Need Technology? - Fonariuk, O.; Malykhin, A.; Murzina, O. A.; Sherman, M.; Kanibolotska, O.; Tynnyi, V.; Мурзіна, Олена Анатоліївна (My University, 2023)
The article defines the concepts of distance education, distance learning and performs their general analysis. Their main forms, types and meanings in the educational system, as well as advantages and disadvantages are considered. The historical foundations of distance learning and all the stages of its formation are clearly traced, followed by the definition of characteristic features. Describes possible ways to eliminate existing problems and improve the quality of such learning. Considerable attention is paid to distance learning technology and its resources, in particular, expanded reality. Its key features, strengths and weaknesses, importance in the educational process and distance education are outlined. To create this article we used methods of synthesis and analysis, historical, comparative, and theoretical analysis of scientific literature and thematic journals and collection of data from sources. To achieve the proposed goal, we used the literature of various scientists and researchers who devoted their works to the subject of distance education. This allowed an in-depth study and research on this topic and came to the conclusion that distance learning is not inferior to traditional and is in increasing demand every year. In turn, expanded reality technology is exactly what the modern student needs to fully immerse himself in the world of learning and make the process exciting, interesting and interactive.
Мурзіна О. А. - https://orcid.org/0000-0002-6968-5525
Keywords: distance education; augmented reality; virtual reality; distance learning technologies; mixed reality; types of distance learning